New public diplomacy in the 21st century : a comparative study of policy and practice - Pamment, James (London Routledge, 2014)
This book examines the concept of new public diplomacy against empirical data derived from three country case studies, in order to offer a systematic assessment of policy and practice in the early 21st century. The new public diplomacy (PD) is a major paradigm shift in international political communication. Globalisation and a new media landscape challenge traditional foreign ministry 'gatekeeper' structures, and foreign ministries can no longer lay claim to being sole or dominant actors in communicating foreign policy. This demands new ways of elucidating foreign policy to a range of nongovernmental international actors, and new ways of evaluating the influence of these communicative efforts. The author investigates the methods and strategies used by five foreign ministries and cultural institutes in three countries as they attempt to adapt their PD practices to the demands of the new public diplomacy environment. Drawing upon case studies of US, British, and Swedish efforts, each chapter covers national policy, current activities, evaluation methods, and examples of individual campaigns. This book will be of much interest to students of public diplomacy, foreign policy, political communication, media studies and international relations in general.
Keywords: Diplomacia; Relaciones internacionales